2017
DOI: 10.1002/ca.23033
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of the superficial temporal artery to prevent facial nerve injury during arterial biopsy

Abstract: To investigate the topographical relationship between the frontal branch of the superficial temporal artery (FSTA) and the temporal branch of the facial nerve (TFN) with the aim of preventing nerve injury during FSTA biopsy. Fifty-seven hemifaces of 33 cadavers were dissected. Vertical lines drawn to the lateral orbital margin (LOM) and the superior root of the helix were used as the anterior and posterior reference positions, respectively. Horizontal lines drawn through the supraorbital margin and lateral can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Focus has been primarily on the relationship between the temporal STVs and the auriculotemporal nerve, as well as on the infrazygomatic STVs and their relationship to the temporal branch of the facial nerve (TBFN). [32][33][34] Importantly, we found no incidence of facial nerve palsy in the clinical cohort undergoing free flap reconstruction with microanastomosis to the intraparotid STVs, demonstrating that the vessels can be safely dissected in this region without nerve damage. On cadaver dissection, the facial nerve entered the parotid on average 11.7 mm inferior to the confluence point (target for microanastomosis).…”
Section: Discussionmentioning
confidence: 64%
“…Focus has been primarily on the relationship between the temporal STVs and the auriculotemporal nerve, as well as on the infrazygomatic STVs and their relationship to the temporal branch of the facial nerve (TBFN). [32][33][34] Importantly, we found no incidence of facial nerve palsy in the clinical cohort undergoing free flap reconstruction with microanastomosis to the intraparotid STVs, demonstrating that the vessels can be safely dissected in this region without nerve damage. On cadaver dissection, the facial nerve entered the parotid on average 11.7 mm inferior to the confluence point (target for microanastomosis).…”
Section: Discussionmentioning
confidence: 64%
“…The superficial temporal fascia is thin in patients with temporal hollowing and confers a great risk to all the neurovascular structures it encompasses. 37,50,51 Several studies in our review reported transient paresthesias secondary to facial nerve damage, but the risk of permanent damage remains unknown.…”
Section: Discussionmentioning
confidence: 97%
“…The superficial temporal artery (STA) is an important continuation of the external carotid artery. It is divided into the frontal branch and the parietal branch at or above the zygomatic arch (1). In neurosurgical practice, the STA is an excellent donor vessel for extracranial-intracranial bypass (2).…”
Section: Introductionmentioning
confidence: 99%